GAMBARAN KEJADIAN MASKNE PADA MASA PANDEMI COVID-19 PADA MAHASISWA TATA RIAS UNESA - Wijaya, Nieke; Novia Restu Windayani; Octaverina Kecvara Prithasari (Universitas Negeri Surabaya, 2022)
Maskne is characterized by the appearance of acne in areas covered by mask, such as cheeks, chin, nose, and jaw. Maskne has become increasingly common since the Covid-19 pandemic, that caused by the highly contagious SARS-CoV-2 virus. One approach to prevent virus spreading is to wear a mask. Using masks for a long time can cause maskne due to increase in humidity and temperature, changes in sebum composition, imbalance of skin microbiota and friction with the mask. This study aims to find out the description of maskne incidence in students of Cosmetology Education at Unesa. The data were obtained through questionnaires, and found that 31 respondents were suffered from maskne. Results showed that 24 students (77.42%) had history of acne. Location of acne is on the chin (38%), cheeks (34%), nose (20%), and jaw (10%). Acne was accompanied by symptoms of redness (53%), itch (42%), and pain (5%). Almost all of respondents used medical masks (96.77%). The majority (80.65%) used masks for 4-8 hours. Majority of respondents regularly clean their faces (96.77%), routinely use skin care (100%), and cosmetics (80.65%) under the mask. Conclusion of this study is that the use of masks for a long time can cause maskne, but masks is still needed to prevent the transmission of Covid-19, so that it is necessary to pay attention related to hygiene, the duration of using masks, using non-comedogenic skin care, to the use of cosmetics that should be limited.